Peranan dan kedudukan perempuan Melayu dalam masyarakat matrilineal Minangkabau di Sumatera Barat - Hermayulis, (Universiti Kebangsaan Malaysia, 2008)
The position of bundo kanduang in Minangkabau customary law is not only that as determinant of descendants, but also manager of rumah gadang and owner of inherited property, thus playing a preeminent role in family economy. In this context, she is expected to possess many characteristics. Among them are that she must be right, honest, intelligent, besides wise and full of endurance